Various Recognition approach in human faces - Karthigayan, M. (Universiti Teknologi Petronas (UTP), 2009)
Organized by Electrical & Electronic Engineering Programme, Universiti Teknologi PETRONAS (UTP), 1st - 3rd December 2005, Kuala Lumpur, Malaysia.